Factors associated with the risk of heart failure progression in patients with non-compaction cardiomyopathy. (14th October 2021) - Rineiska, N; Komissarova, S; Haidzel, I
Abstract: Purpose: To identify factors associated with the progression of chronic heart failure (CHF) to NYHA FC III, requiring hospitalization and to reveal high-risk pts. Methods: The study included 156 pts with non-compaction cardiomyopathy (NCCM), who were prospectively observed in the RSPC "Cardiology". The median follow-up was 36 months (6; 152). All pts underwent echocardiography (Echo), cardiac magnetic resonance (CMR) imaging with late gadolinium enhancement (LGE) and 24-hour Holter monitoring. The median age of the pts was 36 (26; 49) years, men predominated (57.4%). The diagnosis of NCCM was established on the basis of the following criteria: Echo – Jenni criteria, CMR – Petersen/Jaquier criteria. The end point of the study included progression of CHF from NYHA FC II to FC III, requiring hospitalization. Results: At the initial examination, symptoms of CHF NYHA FC I were found in 56 (55.4%) pts, symptoms of CHF NYHA FC II – in 45 (44.6%) pts, systolic dysfunction was detected in 43% of pts. During the follow-up period, out of 156 pts, 55 (35.3%) had CHF symptoms that progressed to NYHA FC III and required hospitalization. As a result of the bivariate analysis, the following Echo characteristics were independent factors associated with a high risk of progression of CHF to NYHA FC III: LV EF <40% (HR 6.2; 95% CI 3.4–11.2); end-diastolic LV diameter >62 mm (HR 5.3; 95% CI 2.9–9.7); end-systolic LV diameter >56 mm (HR 6.6; 95% CI 3.8–11.7); end-diastolic LV volume >187 ml (HR 4.4; 95% CI 2.5–8); end-systolic LV volume >93 ml (HR 6.5; 95% CI 3.2–13). The risk of progression of CHF to NYHA FC III was 3.4 times higher in pts with right ventricular (RV) systolic dysfunction: with a decrease of RV fractional area change (FAC) <31% (HR 3.4; 95% CI 1.8–6.3) and 2.5 times higher with a decrease of tricuspid annular plane systolic excursion (TAPSE) (HR 2.5; 95% CI 1.3–4.5); 2.5 times higher in pts with initially increased anteroposterior RV diameter >28 (HR 2.5; 95% CI 1, 4–4.5). According to the LGE-CMR data, the factors associated with the risk of progression of CHF to NYHA FC III were the following characteristics: an increase of BSA-indexed end-diastolic LV volume >145 ml/m 2 (HR 6.7; 95% CI 3.4–13.3); BSA-indexed end-systolic LV volume >96 ml/m 2 (HR 6.8; 95% CI 3.4–13.6); and an increase of RV end-systolic volume >145 ml (HR 5.0; 95% CI 2.3–11). The risk of CHF progression was 4.8 times higher in pts with baseline LV systolic dysfunction (LV EF <34%, HR 4.8; 95% CI 2.8–8.2); 2.7 times higher in pts with RV systolic dysfunction (LVEF <42%, HR 2.7; 95% CI 1.6–4.8). The NC/C ratio and the presence of myocardial replacement fibrosis according to LGE-CMR did not significantly affect the risk of progression of CHF. Conclusion: The factors identified as a result of the study associated with the risk of progression of CHF based on biventricular assessment by cardiac imaging methods (Echo and LGE-CMR) can be used to reveal high-risk pts. Funding Acknowledgement: Type of funding sources: None.